Involvement of Acetylcholine‐α7nAChR in the Protective Effects of Arterial Baroreflex against Ischemic Stroke - Liu, Ai‐Jun (CNS Neurosci Ther, 2012)
AIMS: Decreased baroreflex sensitivity is associated with poor outcome in many cardiovascular diseases including stroke, but the molecular mechanism underlying this relationship is unclear. This work was designed to test the hypothesis that acetylcholine (ACh) and α7 nicotinic ACh receptor (α7nAChR) mediate the protection of arterial baroreflex against stroke. METHODS: Sinoaortic denervation (SAD) was used to impair the function of arterial baroreflex, and anticholinesterase agents were used to activate the cholinergic system and increase endogenous ACh. Middle cerebral artery occlusion (MCAO) was performed in the α7nAChR knockout (KO) mice and Sprague–Dawley rats. RESULTS: We found decreased expression of vesicular ACh transporter (VAChT) and α7nAChR in rat brain after SAD. In rats subjected to MCAO, neostigmine significantly reduced the infarct size. The protective effects of neostigmine were abolished by selective nAChR antagonist vecuronium but not by mAChR antagonist anisodamine. In addition, the effect of neostigmine disappeared in α7nAChR KO mice. In cultured neurons, ACh inhibited cell death induced by H (2) O (2). In cultured microglial cells, ACh decreased the release of proinflammatory cytokines induced by lipopolysaccharide. These in vitro effects were blocked by selective α7nAChR antagonists. CONCLUSION: Taken together, these findings indicate that the ACh‐α7nAChR involved in the protective effects of arterial baroreflex against ischemic stroke.